The challenges faced by teachers with remote teaching in pandemic times: a case study in the state public network in the city of Parnaiba-PI/Brazil (Research, Society and Development, 2022)
The COVID-19 pandemic has generated significant impacts in all areas, such as health, economy, and education, the latter culminating in the suspension of face-to-face classes. Also, it has reduced the time dedicated to classes and generated numerous problems for teachers, as this has hampered both the transfer of content and the development of the entire teaching-learning process. It is noted that the platforms are used to publish fixed activities, texts, and others, aimed at classes that require more time but which, in short, do not have more excellent aggregate knowledge. This research aimed to analyze the challenges faced by high school teachers, from the state public network of the city of Parnaíba-PI, in the teaching-learning process, at a distance. It used the scientific-technological method to seek answers to the following guiding questions: a) how does distance learning happen in-state public schools in that municipality, b) analyze the strategies and tools used by schools for the operationalization of distance learning, c) identify the methods used, and d) the main difficulties faced by teachers in their distance classes. It is a case study, exploratory-descriptive research, with a qualitative approach. The results showed significant obstacles due to the pandemic's changes, constituting barriers to the learning process being carried out successfully. There are several challenges to overcome in this form of teaching, from the capacity of technical resources to the emotional problems triggered. The analysis showed that the most significant difficulties encountered by teachers during teaching during the Covid-19 pandemic were: 1) lack of quality internet access; 2) lack of motivation; 3) lack of adequate access to technological issues; 4) overwork; 5) lack of interaction with students; 6) socio-emotional issues: uncertainties, anxiety, insecurity.